Old ideas - new perspectives. Debates on multiculturalism and integration (KULT_online, 2014)
Both the study Der Skandal der Vielfalt and the anthology Die Integrationsdebatte zwischen Assimilation und Diversität elaborate on important concepts and debates concerning questions of diversity and cultural differences. The monograph traces the development of multiculturalism, while the anthology provides insights into the discourse of integration. Both complement each other very well and offer a profound overview.